2021
DOI: 10.3390/jcm10081765
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Stent Strut Fractures: Classification, Prevalence and Clinical Associations

Abstract: Introduction. The frequency, characteristics and clinical implications of Strut fractures (SFs) remain incompletely understood. Methods and results. A total of 185 (160 patients) newer-generation drug-eluting stents (DES) were imaged. SFs were found in 21 DES (11.4%) and were classified in four patterns: one single stacked strut (41%); two or more stacked struts (23%); deformation without gap (27%); transection (9%). In multivariable analysis, calcific and bifurcation lesions were associated with SF in DES (OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Similar results were obtained by other studies with an incidence of <1.0% up to 18.6% [10,11,[14][15][16][17][18][19][20]]. An analysis with new generation DES by Schochlow et al [21] showed incidental detection of SF in 8% immediately after implantation and almost 60% in the setting of device failure. The largest multicenter study has been carried out by Kan et al [22] reporting an incidence of SF in 12.3% of the 6555 involved patients, 22.0% of stents and 17.2% of vessels.…”
Section: Incidence Of Stent Fracturessupporting
confidence: 82%
See 1 more Smart Citation
“…Similar results were obtained by other studies with an incidence of <1.0% up to 18.6% [10,11,[14][15][16][17][18][19][20]]. An analysis with new generation DES by Schochlow et al [21] showed incidental detection of SF in 8% immediately after implantation and almost 60% in the setting of device failure. The largest multicenter study has been carried out by Kan et al [22] reporting an incidence of SF in 12.3% of the 6555 involved patients, 22.0% of stents and 17.2% of vessels.…”
Section: Incidence Of Stent Fracturessupporting
confidence: 82%
“…Stent overlap was also significantly associated with SF in the large meta-analysis by Chakravarty et al [13]. Finally, stent overexpansion can exceed material capacity and induce strut distortion causing early fatigue and SF [5,12,21,50]. Omar et al [26] report a mean postdilation pressure of 18 atm (IQR 16-20) in fractured stents.…”
Section: Pathomechanismmentioning
confidence: 99%
“…Titles and abstracts of these records were screened for inclusion. The full texts of 73 records were read, and 46 studies were finally included in the data assessment ( 3 8 , 11 50 ). Figure 1 shows the PRISMA flow diagram describing the study selection process along with the reasons for exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Especially in recent years, the thinner steel beam thickness in the new generation of alloy stents and the wide use of intraluminal imaging technology have led to a significant increase in the incidence of CSF in clinical practice ( 3 5 ). In addition, serious clinical cardiovascular events such as in-stent restenosis (ISR), stent thrombus (ST), coronary artery aneurysm and coronary perforation induced by CSF have threatened patients’ health ( 6 8 ). In addition, trials assessing the incidence of CSF and related risk factors for CSF have recently been published and added to the evidence base.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent case series, our group reported that fracture, classified in four different patterns, typically results in a focal ISR at the fracture point ( Figure 10 ) ( 109 ). In that study, we proposed an OCT-based classification in different patterns of increased severity (from single stacked struts to rupture and gap), and indeed, more complex fracture patterns were more common in the presence of device failure than in incidentally discovered fractures.…”
Section: Prevention Of Restenosismentioning
confidence: 99%